Efficacy of Panax ginseng Meyer Herbal Preparation HRG80 in Preventing and Mitigating Stress-Induced Failure of Cognitive Functions in Healthy Subjects: A Pilot, Randomized, Double-Blind, Placebo-Controlled Crossover Trial - Pierre-Antoine Mariage; Areg Hovhannisyan; Alexander G. Panossian (MDPI AG, 2020)
Background: The aim of this pilot study was to compare the efficacy of hydroponically cultivated red Panax ginseng Meyer root preparation (HRG80) and traditionally harvested six-year-old white P. ginseng standard preparation (PGS) with placebo in preventing symptoms of stress. Methods: The effects of HRG80, PGS, and placebo capsules were studied in 50 tired healthy subjects in a three-arm, randomized, double-blinded, placebo-controlled crossover trial. Efficacy-outcome measures included the accuracy of processing the d2 test for cognitive functions, obtained accuracy score in a computerized memory test, and the perceived-stress (PS) score. Results: A statistically significant interaction effect between time and treatment (p < 0.0001) was observed in the attention d2 and memory tests, indicating that HRG80 treatment was more beneficial than that with a placebo. The effects of PGS were better than those of the placebo, but the difference was not statistically significant. There was significant difference between the effects of HRG80 and PGS (p < 0.0001) that were observed after single (Day 1) and repeated administrations on Days 5 and 12 of treatment. Conclusion: Overall, HRG80 treatment was significantly superior compared to that with the PGS and placebo regarding attention, memory, and PS scores after single and repeated administrations for 5 and 12 days.